Splicing factors Sf3A2 and Prp31 have direct roles in mitotic chromosome segregation - Pellacani, Claudia; Bucciarelli, Elisabetta; Renda, Fioranna; Hayward, Daniel; Palena, Antonella; Chen, Jack; Bonaccorsi, Silvia; Wakefield, James G; Gatti, Maurizio; Somma, Maria Patrizia (eLife, 2018)
Several studies have shown that RNAi-mediated depletion of splicing factors (SFs) results in mitotic abnormalities. However, it is currently unclear whether these abnormalities reflect defective splicing of specific pre-mRNAs or a direct role of the SFs in mitosis. Here, we show that two highly conserved SFs, Sf3A2 and Prp31, are required for chromosome segregation in both Drosophila and human cells. Injections of anti-Sf3A2 and anti-Prp31 antibodies into Drosophila embryos disrupt mitotic division within 1 min, arguing strongly against a splicing-related mitotic function of these factors. We demonstrate that both SFs bind spindle microtubules (MTs) and the Ndc80 complex, which in Sf3A2- and Prp31-depleted cells is not tightly associated with the kinetochores; in HeLa cells the Ndc80/HEC1-SF interaction is restricted to the M phase. These results indicate that Sf3A2 and Prp31 directly regulate interactions among kinetochores, spindle microtubules and the Ndc80 complex in both Drosophila and human cells.